Colonial desire: hybridity in theory, culture, and race - Young, Robert (Routledge, 1995)
In this study, the author argues that today's theories on post-colonialism and ethnicity are disturbingly close to the colonial discourse of the 19th century. He shows how culture has always carried within it an inner dissonance, and 'Englishness' has always been less fixed and stable than uncertain, fissured by difference and a longing for otherness. At the heart of Victorian racial theory, this re-emerges in the form of colonial desire: an obsession with hybridity, focused explicitly on sexuality and the issue of inter-racial unions. This book breaks new ground in analysing how concepts of culture get formed, and how racialized assumptions continue to pervade them.
Includes bibliographical references (p. 206-225) and index.
Hybridity and Diaspora -- Culture and the History of Difference -- The Complicity of Culture Arnolds Ethnographic Politics -- Sex and Inequality: The Cultural Construction of Race -- Egypt in America, The Confederacy In London -- White Power, White Desire: The Political Economy of Miscegenation -- Colonialism and The Desiring Machine.
In this study, the author argues that today's theories on post-colonialism and ethnicity are disturbingly close to the colonial discourse of the 19th century. He shows how culture has always carried within it an inner dissonance, and 'Englishness' has always been less fixed and stable than uncertain, fissured by difference and a longing for otherness. At the heart of Victorian racial theory, this re-emerges in the form of colonial desire: an obsession with hybridity, focused explicitly on sexuality and the issue of inter-racial unions. This book breaks new ground in analysing how concepts of culture get formed, and how racialized assumptions continue to pervade them.
Keywords: Prejudice / history / Great Britain.; Prejudice / history / United States.; Sexual Behavior / history / United States.; Ethnocentrism / Great Britain.; Racism / Great Britain / History.; Sex and history; Race; Miscegenation (Racist theory) / Great Britain / History.; Cultural fusion; United Kingdom; United States; Great Britain / Race relations / History.; History / fast / (OCoLC)fst01411628